Understanding the efficacy of concentrated interstitial carbon in enhancing the pitting corrosion resistance of stainless steel. (December 2021) - Li, Tianshu; Chien, Szu-Chia; Ren, Zhe; Windl, Wolfgang; Ernst, Frank; Frankel, Gerald S.
Abstract: By introducing a high fraction of interstitial carbon through low temperature carburization, the pitting corrosion resistance of austenitic stainless steel can be significantly improved. Previous work attributed this to strengthening of the passive film by carbon. Here, however, we present a paradigm shift by showing that carbon actually weakens the passive film but strengthens the bonding within the alloy by forming localized (covalent) bonds with the metal atoms (Fe, Cr, Ni). Accordingly, the enhancement in pitting resistance is a result of carbon reducing the metal dissolution rate in a local pit environment by many orders of magnitude, which extremely decreases the growth stability of a pit and prevents it from transitioning into stable growth. Electronic structure calculations confirm that carbon bonds to the metal atoms and that the metal–carbon bonds are 1.4 to 2.0 times stronger than the metal–metal bonds. These results suggest a new strategy for the design of corrosion resistant alloys, namely surface engineering by infusion of concentrated interstitials that form strong bonds with the matrix atoms. Graphical abstract: Image, graphical abstract